Postoperativ erhöhter Sauerstoffbedarf und Hämoptysen nach Extubation = Postoperatively increased oxygen demand and hemoptysis after extubation - Kloth, Jost; Wiebel, Matthias; Weber, Marc-André (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2012)
A 22-year-old man on postoperative day 1 after open reduction with internal fixation of a distal fibula fracture presented with hemoptysis and increased oxygen demand. X-ray and contrast-enhanced computed tomography revealed bilateral patchy opacities and mediastinal emphysema. After bronchoscopy and bronchoalveolar lavage, a diagnosis of alveolar hemorrhage was made. The medical history revealed regular abuse of marihuana and cocaine.
Gesehen am 26.10.2018